Pathology and pathogenesis of Vibrio infection in fish: a review - Manchanayake, Tilusha; Salleh, Annas; Azmai, Mohammad Noor Amal; Md Yasin, Ina Salwany; Saad, Mohd Zamri (Elsevier BV, 2023)
Vibrio-associated ailments are important globally, not only among marine aquaculture systems but also among wild fish populations. Vibriosis leads to significant economic losses in fish farms. The disease is generally characterised by external skin lesions, haemorrhages, and septicaemia. Fish or shellfish of any age group are susceptible to the infection but, young animals are more prone. The infection starts with the crucial initial attachment of the bacterium to the host tissue, which is brought about by various virulence factors. This is followed by proliferation and invasion into the internal organ systems through blood circulation. However, the host defence systems provide barriers against the invasion through physical, cellular and chemical mechanisms. Nevertheless, environmental stress might tilt the balance of successful invasion and disease establishment. Therefore, basic knowledge on the pathology and pathogenesis of vibriosis, the virulence factors of the organism and the host defence mechanisms are important in the attempts to control the emergence of vibriosis. In this review, the current knowledge on pathology, histopathology, pathogenesis and virulence factors of Vibrio bacterium is discussed.